PRESTIGE IN THE BUGIS COMMUNITY: WHY CAN'T GOLD JEWELLERY IN BUGIS WOMEN SHIFT SOCIAL STATUS? - Fawziah Zahrawati B; Andi Aras; Poonam Ingle (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
The Bugis people have a social stratification system that is inherited from generation to generation, where a person's social status is determined more by genealogical factors compared to the accumulation of material wealth. This study aims to analyse the relationship between descent and social status in the Bugis community and explore how gold jewellery functions as a symbol of prestige for women. This study uses a qualitative approach with data collection techniques including in-depth interviews, observations, and documentation in Wajo Regency, South Sulawesi. This study applies triangulation techniques by combining in-depth interviews, observations, and documentation, as well as time triangulation, to avoid temporal bias. Data analysis uses the Miles and Huberman approach through three main stages: data reduction, data presentation, and conclusion drawing and verification. The results of the study show that in the Bugis community, the social stratification system is still based on lineage, while gold functions more as a status symbol for those who already have a certain social position, rather than as a tool of social mobility. The symbolism of gold jewellery is subject to established social structures, so the prestige gained through gold is not strong enough to shift the social stratification that has been inherited.